Electro-mechanical dysfunction in long QT syndrome: Role for arrhythmogenic risk prediction and modulation by sex and sex hormones. Issue 1 (January 2016) - Lang, C.N.; Menza, M.; Jochem, S.; Franke, G.; Perez Feliz, S.; Brunner, M.; Koren, G.; Zehender, M.; Bugger, H.; Jung, B.A.; Foell, D.; Bode, C.; et al.
Abstract: Long QT syndrome (LQTS) is a congenital arrhythmogenic channelopathy characterized by impaired cardiac repolarization. Increasing evidence supports the notion that LQTS is not purely an "electrical" disease but rather an "electro-mechanical" disease with regionally heterogeneously impaired electrical and mechanical cardiac function. In the first part, this article reviews current knowledge on electro-mechanical (dys)function in LQTS, clinical consequences of the observed electro-mechanical dysfunction, and potential underlying mechanisms. Since several novel imaging techniques – Strain Echocardiography (SE) and Magnetic Resonance Tissue Phase Mapping (TPM) – are applied in clinical and experimental settings to assess the (regional) mechanical function, advantages of these non-invasive techniques and their feasibility in the clinical routine are particularly highlighted. The second part provides novel insights into sex differences and sex hormone effects on electro-mechanical cardiac function in a transgenic LQT2 rabbit model. Here we demonstrate that female LQT2 rabbits exhibit a prolonged time to diastolic peak – as marker for contraction duration and early relaxation – compared to males. Chronic estradiol-treatment enhances these differences in time to diastolic peak even more and additionally increases the risk for ventricular arrhythmia. Importantly, time to diastolic peak is particularly prolonged in rabbits exhibiting ventricular arrhythmia – regardless of hormone treatment – contrasting with a lack of differences in QT duration between symptomatic and asymptomatic LQT2 rabbits. This indicates the potential added value of the assessment of mechanical dysfunction in future risk stratification of LQTS patients.